Relation between magnetopause position and reconnection rate under quasi-steady solar wind dynamic pressure - Hyangpyo Kim; Hyunju Kim Connor; Ying Zou; Jaeheung Park; Rumi Nakamura; Kathryn McWilliams (Earth, Planets and Space, 2024)
Abstract The lunar environment heliospheric X-ray imager (LEXI) and solar wind–magnetosphere–ionosphere link explorer (SMILE) will observe the magnetopause motion in soft X-rays to understand dayside reconnection modes as a function of solar wind conditions after their respective launches in the near future. To support their successful science mission, we investigate the relationship between the magnetopause position and the dayside reconnection rate by utilizing super dual auroral radar network (SuperDARN) observations and widely used empirical models of magnetopause position (Shue et al. in J Geophys Res 103:17691–17700. https://doi.org/10.1029/98JA01103 , 1998 and Lin et al. in J Geophys Res 115:A04207. https://doi.org/10.1029/2009JA014235 , 2010). We select three cases when the interplanetary magnetic field rotates during periods of quasi-steady solar wind dynamic pressure. We first estimate the dayside reconnection rate by calculating the electric field along the open–closed magnetic field boundary (OCB) in the OCB moving reference frame. Then, we estimate the magnetopause position near the local noon by inputting NASA OMNI solar wind data into the empirical magnetopause models. The reconnection rate shows anti-correlation with the magnetopause position that it generally increases as the magnetopause located closer to Earth and vice versa. Our result also confirms that the reconnection rate increases as the empirical coupling efficiency between solar wind and the magnetosphere increases. Graphical abstract